Analisis Pengaruh Jumlah Penduduk Dan Penanaman Modal Asing Terhadap Pertumbuhan Ekonomi Di Kabupaten /Kota Provinsi Kalimantan Tengah - Alexandra Hukom; Ayu Mei Duma Pakpahan; Augusta Rowa; Senihati Telaumbanua; Renanda Indah Doharma Silalahi; Agustina Dirgahayu; Lisia Cermin Dongoran; Jonathan Pedlik Perjaka; Elisabeth Sinaga; Friskilla Wulandari; Marinus Juanlix Ato (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of population and foreign investment on economic growth in the district / city of Central Kalimantan Province. By using time series panel data from 2019 to 2024 and a quantitative approach, with the Vector Error Correction Model (VECM) analysis method on secondary data from the Central Kalimantan Statistics Agency (BPS). The results showed that population has a positive and significant effect on economic growth in the long term, indicating that good human resource management can be a driver of economic growth, Conversely, foreign investment actually shows a significant negative effect on economic growth in the long term. In the short term, there is no strong significant effect between these variables, except from the past value of the variable itself. The Granger causality test indicates a two-way relationship between population and economic growth, as well as a one-way relationship from economic growth to foreign investment.The results of this research analysis indicate that optimizing the potential of population and managing foreign investment strategically is needed to encourage inclusive and sustainable economic growth in Central Kalimantan. The findings are expected to be an input for regional policy makers in designing demography-based development strategies in Central Kalimantan. The findings are expected to be an input for regional policy makers in designing development strategies based on demographics and foreign investment.